Optical properties of poly(9,9’-di-n-octylfluorenyl-2.7-diyl)/amorphous SiO2 nanocomposite thin films - Mohammad Hafizuddin Haji Jumali,; Bandar Ali Al-Asbahi,; Chi, Chin Yap; Muhamad Mat Salleh,; Mohamad Saleh Alsalhi, (Universiti Kebangsaan Malaysia, 2013)
Identified as potential materials for optoelectronic applications, the polymer/inorganic nanocomposites are actively studied. In this work, the effect of amorphous silica nanoparticles (NPs) content on the optical properties of Poly (9,9’-di-n-octylfluorenyl- 2.7-diyl) (PFO) thin films has been investigated. Different ratios of PFO/SiO2 NPs composites have been prepared using solution blending method. Then, the blends were spin-coated onto glass substrates at 2000 rpm for 30 s and subsequently dried at room temperature. XRD and TEM were used to determine the structural properties, while UV-Vis and PL spectrophotometers were employed to investigate the optical properties of the films. XRD confirms that there was no variation on structure of both PFO and SiO2 NPs resulted from the blending process. TEM micrographs display that majority of amorphous SiO2 NPs were well coated with PFO. The absorption spectra of the composite thin films were red-shifted, indicating the increment in conjugation length of the PFO/SiO2 composite. In addition, the calculated values of the optical energy gap, the width of the energy tails and vibronic spacing of the composite films exhibited SiO2 content dependence.